O grupo como estratégia terapêutica nos Centros de Atenção Psicossocial Álcool e Drogas do Espírito Santo - Santos, Élem Guimaraes dos (2010)
The objective of this study is to describe the joint assistance provided by the graduated professionals in the “Centers for Psychosocial Attention to Drugs and Alcohol Users” (CAPSad) of the Espírito Santo state in Brazil. A descriptiveexploratory study of qualitative type was performed in order to describe it. The adopted technique adopted for data collection was a semi structured interview. The three Centers for Psychosocial Attention to Drugs and Alcohol were the scenarios where 17 graduated professionals of different categories were interviewed. The interviews were transcribed and all the qualitative material were submitted to content analysis, which resulted in 4 analyses categories; group conceptions, methodologies adopted in the groups difficulties found in the groups and professional training and preparation for the work with groups. The results of this research show that group work is a very common used strategy by all the CAPSad which receive different denominations depending on their goal and context and are coordinated by professionals of different areas. The groups actions are performed through several methodologies depending on the type of group, the available resources and the theory referential adopted by the coordinating professional. The main difficulties faced by the groups were associated to the patients, the professionals, the lack of resources and the group process. Concerning the professional training it was observed that the group work experience with the psychoactive substance users drive the professionals to many challenges and most frequently these professionals are not prepared to handle which strongly influences their practices. Whereupon the study concludes that the work done in groups constitute important strategies in the caring of the psychoactive substance users, being practices not widely systematized in these contexts.